THE RELATIONSHIP BETWEEN SCHOOL CLIMATE AND LEARNING MOTIVATION WITH STUDENTS' LEARNING ACHIEVEMENT OF SMP NEGERI 7 DARUL MAKMUR NAGAN RAYA - Petro Satriwo; Saiful Akhyar Lubis; Salamiah Sari Dewi (RADJA PUBLIKA, 2023)
This study aims to determine the relationship between school climate and learning motivation with student achievement at SMP Negeri 7 Darul Makmur Nagan Raya. The subjects in this study were 48 students of SMP Negeri 7 Darul Makmur Nagan Raya. The sample collection method uses the Simple Random Sampling technique. Learning achievement is measured by grades (learning outcomes) and school climate is measured by a scale of school climate aspects which consists of 19 valid items, while learning motivation is measured by a scale of aspects of learning motivation which consists of 18 valid items. The data analysis used is multiple regression for the first hypothesis and partial correlation test for the second and third hypotheses.